2010
DOI: 10.1111/j.1476-5381.2010.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain attenuates cardiotoxicity induced by other cardiac steroids

Abstract: Background and purpose: All cardiac steroids have a similar structure, bind to and inhibit the ubiquitous transmembrane protein Na + , K + -ATPase and increase the force of contraction of heart muscle. However, there are diverse biological responses to different cardiac steroids both at the cellular and at the molecular level. Moreover, we have recently shown that ouabain inhibits digoxin-and bufalin-induced changes in membrane traffic. The present study was designed to test the hypothesis that ouabain also ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…6). Furthermore, in a study of the activity of CS on heart muscle contractility and rhythm, it was shown that different CS are even antagonistic to the effects of others (47). This diversity of action of the different CS may be of significance when considering the putative physiological roles of the different ECS.…”
Section: Discussionmentioning
confidence: 98%
“…6). Furthermore, in a study of the activity of CS on heart muscle contractility and rhythm, it was shown that different CS are even antagonistic to the effects of others (47). This diversity of action of the different CS may be of significance when considering the putative physiological roles of the different ECS.…”
Section: Discussionmentioning
confidence: 98%
“…Thus this was "a surprise" in 1993. Nesher and colleagues (31) confirmed that ouabain and digoxin antagonize one another acutely but didn't address the mechanism (41). The mechanism for antagonizing the chronic effects of ouabain (26,27), not studied by Nesher, is apparently more complex (47).…”
Section: Mordecai P Blausteinmentioning
confidence: 86%
“…was published online 4 days before Lewis and colleagues'(21); see our responses toLewis et al (2a,14)]; and 3) called the 1993 discovery of ouabaindigoxin antagonism (27) "a surprise," despite the 2010 report that ouabain antagonizes acute digoxin and bufalin cardiotoxicity(31).…”
mentioning
confidence: 95%
“…Although digoxin is a potent Na-K-ATPase inhibitor, similar to ouabain, there are some important differences between the two agents [8,13,14]. Although digoxin is a potent Na-K-ATPase inhibitor, similar to ouabain, there are some important differences between the two agents [8,13,14].…”
Section: Discussionmentioning
confidence: 99%